2019
DOI: 10.21608/epsj.2019.29811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Moringa Oleifera Leaves on Productive Performance and Some Physiological Parameters of Japanese Quail

Abstract: A total number of eighty four unsexed 7 day old Japanese quail chicks were randomly divided into among four 4 dietary treatments with 3 replicate (7 birds), assigning experimental unit to investigate the effect of feeding Japanese quail chicks on diets containing different levels of Moringa oleifera leaves (MOL) on productive performance, blood constituents, hormones, antioxidant indices, immunity parameters and carcass characteristics. Dietary treatments were: The first group (control) fed a basal diet, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…An improved FCR for Japanese quail which were given M. oleifera leaf meal at the rate of 0.1% was found by Kulkarni et al [ 85 ]. Ahmed and El-Rayes [ 64 ] found that Japanese quail which were fed M. oleifera leaf meal at 3, 5, and 7 g/kg in their diet had an increased FCR and feed intake when compared to the control group that did not receive any supplementation. According to Castillo et al [ 72 ], there was a substantial increase in the FCR for Japanese quail which were given M. oleifera leaf flour at the concentration of 7, 14, and 21%, but showed no significant change in feed consumption.…”
Section: Feed Intake and Efficiencymentioning
confidence: 99%
See 3 more Smart Citations
“…An improved FCR for Japanese quail which were given M. oleifera leaf meal at the rate of 0.1% was found by Kulkarni et al [ 85 ]. Ahmed and El-Rayes [ 64 ] found that Japanese quail which were fed M. oleifera leaf meal at 3, 5, and 7 g/kg in their diet had an increased FCR and feed intake when compared to the control group that did not receive any supplementation. According to Castillo et al [ 72 ], there was a substantial increase in the FCR for Japanese quail which were given M. oleifera leaf flour at the concentration of 7, 14, and 21%, but showed no significant change in feed consumption.…”
Section: Feed Intake and Efficiencymentioning
confidence: 99%
“…According to Kulkarni et al [ 85 ], Japanese quail which were fed M. oleifera leaf meal at a rate of 0.1% gained significantly more weight than the control group. According to Ahmed and El-Rayes [ 64 ], when Japanese quail were fed M. oleifera leaf meal at 3, 5, and 7 g/kg of their diet, a substantial increase in weight gain was found when compared to the control group that did not receive any supplementation. Castillo et al [ 72 ] reported a substantial reduction in weight gain in Japanese quail which were given M. oleifera leaf flour at 7, 14, and 21%.…”
Section: Growth Performance and Body Weight Gainmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the use of phytogenic plant products in their diets would enhance feed utilization efficiency, thereby facilitating sustainable large-scale intensification for safe, healthy, and high-quality quail products (Mahlake et al, 2021). Phytogenic products such as Moringa oleifera leaf meal (MOLM) can be incorporated in Jumbo quail diets as a source of nutrients and functionally active substances (Ahmed and El-Rayes, 2019) such as protein, amino acids, omega−3 fatty acids, vitamins A and C, antioxidants, calcium, iron, potassium, and phosphorous (Onunkwo and George, 2015;Trigo et al, 2020). The antioxidant compounds (phenols, flavonoids, vitamin C, vitamin E, b-carotene, zinc, and selenium) in M. oleifera leaves are said to improve stability and the quality of meat products (Valeria and Williams, 2011).…”
Section: Introductionmentioning
confidence: 99%